Pengaruh Customer Experience dan Destination Image Terhadap Custome Satisfaction dan Revisit Intention: Studi pada Pengunjung Wisata Sawah Sumber Gempong Trawas Mojokerto Fernandito Putra Perdana, Any Urwatul Wusko, Kholid Mutadlo Universitas Yudharta Pa - Fernandito Putra Perdana; Any Urwatul Wusko; Kholid Mutadlo (MES Management Journal, 2025)
This research aims to determine the influence of customer experience and destination image on customer satisfaction and revisit intention at the Sawah Sumber Gempong Trawas Mojokerto tourist attraction. This research uses quantitative methods. The data collection technique in this research uses questionnaires distributed directly or offline. The sample in this research were visitors who visited the Sumber Gempong Sawah tourist attraction with a total sample of 100 respondents who were taken using a purposive sampling method, namely determining the sample where the people selected as samples were in accordance with the aim of the research. The analysis method used is Statistical Package for the Social Sciences (SPSS) analysis with the help of the IBM SPSS Statistics 22 application The results of this research show that customer experience has a positive and significant effect on customer satisfaction, destination image has a positive and significant effect on customer satisfaction, customer experience has a positive and significant effect on revisit intention, destination image has a positive and significant effect on revisit intention, and customer satisfaction has a positive effect and significant for revisit intention